"Community Empowerment for the Development of Margamulya Village Tourism: Sustainable Strategies through Training, Branding, and Technology" - Windya Giri, Refi Rifaldi; Millanyani, Heppy; Dewi, Andrieta Shintia (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
Margamulya Village has significant yet untapped tourism potential. This community service program aims to enhance the capacity and knowledge of the local community in managing and developing the village's tourism potential. The methods used include intensive training on the application of information and communication technology (ICT) and collaboration with various stakeholders. The training covers the identification of tourism potential, destination management, branding strategies, and content creation. The results show a significant increase in the community's ability to manage and promote village tourism, create a strong brand identity, and produce effective marketing content. The program's sustainability is supported by local capacity building, ICT application, strategic collaboration, and the development of resilient tourism business models. This program is expected to serve as a model for sustainable village tourism development in Indonesia and beyond, offering a holistic approach that combines ICT training, branding strategies, and multi-stakeholder collaboration.ABSTRAKDesa Margamulya memiliki potensi wisata yang besar namun belum tergali sepenuhnya. Program pengabdian ini bertujuan untuk meningkatkan kapasitas dan pengetahuan masyarakat lokal dalam mengelola dan mengembangkan potensi wisata desa. Metode yang digunakan meliputi pelatihan intensif penerapan teknologi informasi dan komunikasi (TIK) serta kolaborasi dengan berbagai stakeholder. Pelatihan meliputi identifikasi potensi wisata, manajemen destinasi wisata, strategi branding, dan pembuatan konten. Hasil dari program ini menunjukkan peningkatan signifikan dalam kemampuan masyarakat untuk mengelola dan mempromosikan wisata desa, menciptakan identitas merk yang kuat, dan menghasilkan konten pemasaran yang efektif. Keberlanjutan program didukung oleh penguatan kapasitas lokal, penerapan TIK, kolaborasi strategis, dan pengembangan model bisnis wisata yang resilien. Program ini diharapkan dapat menjadi model bagi pengembangan wisata desa yang berkelanjutan di Indonesia dan di luar negeri, menawarkan pendekatan holistik yang menggabungkan pelatihan TIK, strategi branding, dan kolaborasi multi-stakeholder.